How to kill your roommates and get away with it [videorecording (DVD)] - Cinaglia, Nicole; Sullivan, Lara Jean; Johnson, Hunter; Reingrover, Eric (Tiberiusfilm LLC, 2022)
Done with an '80s vibe, this bloody and surprising dark comedy/thriller tells a story of Ellie who has had it with her roommates and is ready to take a drastic action. With the help of her best friend, the two start plotting ways to get out of her miserable living situation and not get caught. But one mistake may bring a full force of the law down on them.